Aspergillus flavus endocarditis and meningitis in a child with marfan syndrome - Azam Fattahi; Shirin Sayyahfar; Ensieh Lotfali; Reza Ghasemi; Hojjat Mortezaeian (Mazandaran University of Medical Sciences, 2020)
Background and Purpose: Aspergillus species are implicated as the etiology of approximately 26% of endocarditis cases. Central nervous system aspergillosis is a life-threatening condition that has a mortality rate of 80%. Case report: Herein, we report a four- year- old female who was admitted to the pediatric infectious ward due to a fever of unknown origin in January 2020. She was a known case of Marfan syndrome with a family history of this syndrome in her mother. The species was identified using (PCR) and the antifungal susceptibility test was performed using four antifungal agents based on the Clinical and Laboratory Standards Institute M38 3rd edition. Fluconazole-resistant Aspergillus flavus was identified to be responsible for endocarditis and meningitis as well as fever of unknown origin. Conclusion: The clinicians should be aware and consider fungal endocarditis in blood culture-negative endocarditis even in patients with no significant risk factor when antibiotic therapy fails.